Enterococcus faecium as a causative agent of death of Small-Tailed Han sheep farmed in Tongliao region of China: A case study - Meng, Q; Jian, R; Jia, W; Chen, Y; Liu, Z; Zhang, X; Jia, Z; Cui, J; Wang, X (Journal of the Hellenic Veterinary Medical Society, 2025)
In order to determine the cause of death of 27 Small-Tailed Han sheep in a Small-Tailed Han sheep farm in Tongliao, China, we characterized Gram-positive coccobacillus isolated from dead Small-Tailed Han sheep. We have also conducted a preliminary study on the resistance mechanism and pathogenesis of the pathogen. In this study, substantial organs (heart, liver, spleen and kidney) of infected and dead sheep and blood samples of sick sheep were used as test materials. Tests such as isolation and culture of bacteria, antimicrobial susceptibility test, 16S rDNA gene identification, resistance genes detection, and pathological section observation were performed. Better growth of isolated strain on sheep blood agar medium was observed. Antimicrobial susceptibility test found florfenicol (25 mm) and amikacin (25 mm) to have the best bacteriostatic effect. The isolated strain (GenBank sequence number OP430848.1) showed 99.90% similarity to the 16S rDNA fragment of Enterococcus faecium published on GenBank. The isolate was found to harbor cfr, tetM, and ant(6)-I resistance genes. The results of pathological tissue sections showed pathological changes in the substantial organs (heart, liver, spleen and kidney) of the diseased sheep. This test provides a reference for the diagnosis, treatment, and resistance investigation of pathogenic Enterococcus faecium of sheep origin.